Apathy in Parkinson's disease is associated with nucleus accumbens atrophy: A magnetic resonance imaging shape analysis. Issue 7 (10th May 2014) - Carriere, Nicolas; Besson, Pierre; Dujardin, Kathy; Duhamel, Alain; Defebvre, Luc; Delmaire, Christine; Devos, David
ABSTRACT Apathy is characterized by lack of interest, loss of initiative, and flattening of affect. It is a frequent, very disabling nonmotor complication of Parkinson's disease (PD). The condition may notably occur when dopaminergic medications are tapered after the initiation of subthalamic stimulation and thus can be referred to as "dopaminergic apathy." Even in the absence of tapering, some patients may develop a form of apathy as PD progresses. This form is often related to cognitive decline and does not respond to dopaminergic medications (dopa‐resistant apathy). We aimed at determining whether dopa‐resistant apathy in PD is related to striatofrontal morphological changes. We compared the shape of the striatum (using spherical harmonic parameterization and sampling in a three‐dimensional point distribution model [SPHARM‐PDM]), cortical thickness, and fractional anisotropy (using tract‐based spatial statistics) in 10 consecutive patients with dopamine‐refractory apathy, 10 matched nonapathetic PD patients and 10 healthy controls. Apathy in PD was associated with atrophy of the left nucleus accumbens. The SPHARM‐PDM analysis highlighted (1) a positive correlation between the severity of apathy and atrophy of the left nucleus accumbens, (2) greater atrophy of the dorsolateral head of the left caudate in apathetic patients than in nonapathetic patients, and (3) greater atrophy in the bilateral nucleus accumbens in apathetic patients than in controls. There were no significant intergroup differences in cortical thickness or fractional anisotropy. Dopa‐resistant apathy in PD was associated with atrophy of the left nucleus accumbens and the dorsolateral head of the left caudate. © 2014 International Parkinson and Movement Disorder Society